Characterization of palladium electrodeposition in ammonia‐free electrolyte with additives. (26th August 2021) - Oh, In‐Chan; Kim, Ho‐Young; Hyun, Soong‐Keun; Byoun, Young‐Min
Abstract : Electrodeposition of Pd provides excellent chemical and low‐contact resistance with good electrical properties, such as different types of electrical contacts in the electronics industry. The conventional Pd plating process utilizes ammonia‐based electrolytes. Ammonia was added continuously to maintain the optimum pH range in Pd electrolyte. In addition, the harmful and strong odor of the evaporating ammonia necessitates the use of a ventilator. A further disadvantage is that the brass substrate is corroded by ammonia vapor, and the corrosion products can contaminate the electrolytes, thereby changing the technological properties of the deposited plating for the worse. Ethylenediamine has been proposed as an alternative to ammonia; however, Pd electrodeposition occurs as microcracks via hydrogen evolution. In this study, the effects of Pd electrolyte on ethylenediamine as a complexing agent and the properties of various additives are investigated to improve current density and internal stress in Pd electrodeposition that occurs on a brass substrate. Therefore, complexing agents such as 3‐pyridine sulfonic acid, sodium nicotinate, butyne 1–4 diol, and sodium allylsulfonate are selected as additives, to serve as an alternative to ammonia in Pd electrolyte. In this study, the properties of electrodeposited Pd with various additives were examined. The effect of additives on Pd electrolytes can be classified as dense surfaces without defects such as microcracks and pinholes, which improved surface roughness and corrosion resistance. Particularly, Pd electrolyte using sodium nicotinate has relatively improved surface roughness and properties. Pd electrolyte was optimized under ammonia‐free conditions by the addition of sodium nicotinate.